(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Crohn’s disease is an inflammatory bowel disease, which may be associated with a variety of extraintestinal complications, including ocular involvement. However, retinal vascular involvement is noted to be uncommon. We present 2 rare cases of retinal vein occlusion associated with Crohn’s disease.